Delirium after transcatheter aortic valve implantation via the femoral or apical route1. (29th June 2016) - Sharma, V.; Katznelson, R.; Horlick, E.; Osten, M.; Styra, R.; Cusimano, R. J.; Carroll, J.; Djaiani, G.
Summary: We thought that delirium might be less frequent after transcatheter aortic valve implantation via the femoral artery compared with via the cardiac apex. We reviewed 210 patients who underwent transcatheter aortic valve implantation between January 2009 and October 2014. The proportion (95% CI) of patients who suffered delirium in the 3 days after valve implantation were: 10 (3–16%) in 105 patients who had transfemoral implantation; and 35 (25–45%) in 105 patients who had transapical implantation, p = 0.0001. The variables that independently associated with postoperative delirium were age, male sex and the transapical approach. The median (IQR [range]) hospital stay was 7 (5–13 [2–41]) days and 10 (7–15 [2–64]) days, respectively, p = 0.004. Future trials should focus on different peri‐operative management strategies to reduce delirium rates after transcatheter aortic valve implantation, particularly in older men having implantations via the cardiac apex.